Optimal Banach Function Space for a Given Cone of Decreasing Functions in a Weighted \( L_p \)-Space - Bakhtigareeva, Elza (Eurasian Mathematical Journal, 2015)
The problem is considered of constructing optimal (i.e. minimal) generalized Banach function space or optimal Banach function space, containing the given cone of nonnegative, decreasing functions in a weighted Lebesgue space.